Local strain energy density for the fracture assessment of polyurethane specimens weakened by notches of different shape - M. Peron; SMJ. Razavi; F. Berto; J. Torgersen; L. Marsavina (Fracture and Structural Integrity)
Recent studies on local stress fields in proximity of crack and notch tips have shown that Strain Energy Density (SED), averaged in a circular control volume surrounding the point of stress singularities, represents a reliable engineering approach for assessing the brittle fracture of several brittle materials. It is worthy of notice that the application of SED criterion and the reliability of its results are strictly related to the proper determination of fracture parameters, i.e. the critical value of deformation energy Wc and the radius Rc of the control volume. This work presents an experimental methodology for their determination by means of notched specimens for different polyurethane densities, ranging from 100 to 651 kg/m3. Then, once obtained these critical parameters, the failure load in different types of notches and cracked specimens under mode I have been predicted. Moreover, for cracked specimens under mixed mode and mode II, the authors propose a personal approach that confirms PUR foams can be treated as brittle materials